Europe and the Americas : toward a TAFTA - South? - Schott, Jeffrey J. (2001)
Examines Europe's trade and investment ties with Latin America and the Caribbean and prospects for the evolution of a TAFTA-South accord. Summaries the progress to date in the various bilateral and regional trade initiatives. Analyses bilateral trade and investment flows to determine each side's interests and objectives in pursuing free trade talks. Comments on the implication of European-Latin American trade arrangements for US-EU relations and for the FTAA negotiations.